Evaluation of the My Life My Choice (MLMC) Program for Victims of Sex Trafficking, Connecticut, Florida, Massachusetts, and New Jersey, 2015-2018 - Rothman, Emily F. ([Verlag nicht ermittelbar], 2021)
Commercial sexual exploitation (CSE) is an increasingly urgent problem for criminal justice systems in the United States. Despite the staggering individual and societal consequences of CSE, evidence-based prevention and intervention programs are profoundly lacking. This study used a quasi-experimental, mixed methods, longitudinal follow-up design to evaluate a service provision program for CSE survivors or those identified as high-risk for CSE, My Life My Choice (MLMC). Researchers followed youth who received MLMC services from baseline to multiple follow-up points to see how they progressed over time in terms of building up resistance to being sexually exploited. Youth received one of two different type of MLMC services. One group (Source 1) received one-on-one survivor mentoring, otherwise known as "tertiary prevention." Participants in this program are paired with mentors who have been trained and free from CSE for at least five years. Mentors provide long-term and consistent emotional support to exploited youth or those MLMC believes are at high-risk for exploitation. The Source 1 youth were recruited only from Massachusetts. They participated in quantitative and qualitative data collection at baseline, six months post-baseline, and 12 months post-baseline. A second group (Source 2) received 3-10 sessions of a psychoeducational prevention group following the MLMC curriculum, otherwise known as "secondary prevention." These groups are led by trained facilitators and are intended for youth at high-risk for exploitation. Participants are taught about sexual exploitation, healthy relationships, sexual health, and how to find help. Source 2 youth received MLMC services in Massachusetts, Florida, New Jersey, or Connecticut. They participated in quantitative data collection at baseline, time of the last group session, and six months post-baseline. Measured outcomes included instances of sexual exploitation in the past six months, frequency and type of substance use, partner abuse victimization, and housing stability. Researchers hypothesized that, among the secondary prevention group, youth who chose to interact with MLMC staff more often (in terms of attending educational sessions) would score higher on desired outcomes than those frequently absent or who do not interact with staff as often. Among the tertiary prevention group, researchers hypothesized that those who participated would demonstrate improved outcomes from baseline to six months and baseline to 12 months.